Casual But Sunnah: Zaafer Indonesia and the Metamorphosis of the Robe as Fashion in Urban Muslim Communities in Indonesia - Candra, Putri Berliana; Atikurrahman, Moh; Gilia Indriyani, Jiphie (Universitas Islam Negeri (UIN) Mataram, 2023)
This article discusses the shift in the image of robes from Muslim clothing (sacred or religious) to casual clothing (profane or everyday). In the context of this article, the robes produced by Zaafer Indonesia represent a change in the orientation of Indonesian Muslim OOTD from initially tending to be conservative to becoming fashionable and stylish. In this research, clothing is considered a complex sign system. On a piece of clothing, there is a message that the wearer wants to convey. By using the Saussurean semiology paradigm, this article understands that in clothing there is a system of signifiers and signifieds. Clothing is a language (language of fashion) that is built from the language and parole system. The research results show several semiotics in the robes of Zaafer Indonesia products. There is Saussure's synchronic linguistic concept, which is related to several dichotomies, such as signifier, signified, parole, and langue